Novel Maneuver for Endobronchial Fogarty Embolectomy Catheter Placement for Lung Isolation in Infants: An Experience of Four Cases - Baidya, Dalim K.; Pawar, Dilip K.; Maitra, Souvik; Bajpai, Minu; Panda, Shasanka Sekhar (European Journal of Pediatric Surgery, 2015)
One-lung anesthesia in infant is always a challenge to the pediatric anesthesiologist. Thoracoscopic diaphragmatic eventration repair requires high quality of lung isolation for proper surgical access. We are reporting a new technique of lung isolation by Fogarty embolectomy catheter alongside the endotracheal tube in four infants.
Keywords: infant; one-lung ventilation; Fogarty catheter